Resistance against Bacillus thuringiensis endotoxins in a laboratory population of Helicoverpa armigera is based on an elevated immune status - Muhammad Sarjan; Mahbub M Rahman; Gang Ma; Otto Schmit (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2009)
Recent observations suggest that lectin-like toxins, such as endotoxins from Bacillus thuringiensis are sequestered inside the gut of immune-induced insects providing tolerance to Bt-formulations. To investigate the induction and sequestration process, we used toxin and lectins that bind to galactosamine (Gal) and N-acetylagalactosamine (GalNAc) to identify binding sites in the midgut of induced and non-induced insects using confocal microscopy. Our observations suggest that immune and metabolic hemolymph components are transported across the gut epithelium and accumulate inside the gut lumen in Bt-tolerant insects. Co-location of immune components and toxin indicates that some of the toxin is inactivated by coagulation reactions inside the gut lumen before it can reach the brush border membrane